Soil Fertility Status, Nutrient Uptake, And Soybean Yield Following OrganicPLUS Fertilizer Application On Alfisol - Slamet Minardi; Sudadi Sudadi; Ongko Cahyono; Vita Ratri Cahyani; Siti Maro'ah; Isna Luthfa Haniati; Lidya Zaela Wijaya (Agrosains : Jurnal Penelitian Agronomi, 2024)
This study aims to assess the impact of Organic FertilizerPlus on soil fertility status, nutrient uptake, and soybean yield in Alfisol. The research employs a randomized complete group design (RCGD) with a single factor, consisting of P0 (Control), P1 (Cow dung, 5 tons ha-1 + Zeolite dose of 2.5 tons ha-1), P2 (Cow dung, 5 tons ha-1 + Zeolite dose of 5 tons ha-1), P3 (Cow dung, 5 tons ha-1 + Dolomite dose of 2.5 tons ha-1), P4 (Cow dung, 5 tons ha-1 + Dolomite dose of 5 tons ha-1), and P5 (Cow dung, 5 tons ha-1 + Zeolite dose of 5 tons ha-1 + Dolomite dose of 5 tons ha-1), repeated four times. The results indicate that the application of Organic FertilizerPlus enhances soil fertility status (pH, organic C, CEC, and available P), with the highest values observed in treatment P5, including pH (6.70), soil organic C (6.28 g.kg-1), cation exchange capacity (CEC) (6.85 cmol.g-1), and available P (2.63 mg.g-1). This leads to increased phosphorus uptake, consequently improving soybean yields. The highest soybean yield is achieved by applying Organic FertilizerPlus (P5) at 2.17 t.ha-1.